Collectivity in 196, 198Pb isotopes probed in Coulomb-excitation experiments at REX-ISOLDE. (3rd May 2017) - Pakarinen, J; Grahn, T; Gaffney, L P; Algora, A; Bauer, C; Blazhev, A; Bree, N; Cocolios, T E; Witte, H De; Diriken, J; Fernier, P; Hadyńska-Klȩk, K; et al.
Abstract: The neutron-deficient 196, 198 Pb isotopes have been studied in Coulomb-excitation experiments employing the Miniball γ -ray spectrometer and radioactive ion beams from the REX-ISOLDE post-accelerator at CERN. The reduced transition probabilities of the first excited 2 + states in 196 Pb and 198 Pb nuclei have been measured for the first time. Values of B ( E 2 ) = 18.2 − 4.1 + 4.8 W.u. and B ( E 2 ) = 13.1 − 3.5 + 4.9 W.u., were obtained, respectively. The experiment sheds light on the development of collectivity when moving from the regime governed by the generalised seniority scheme to a region, where intruding structures, associated with different deformed shapes, start to come down in energy and approach the spherical ground state.